2020
DOI: 10.1016/j.onehlt.2020.100169
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the global and continental burden of animal tuberculosis in key livestock species worldwide: A meta-analysis study

Abstract: Zoonotic animal tuberculosis (TB) is a One Health paradigm infectious disease, caused by Mycobacterium tuberculosis complex bacteria, that affects different host species with varying levels of management. In most developed countries, official surveillance and control strategies support the longitudinal reporting of herd and/or animal prevalence. However, for under resourced countries without surveillance plans, this information may be obtained from cross-sectional studies only. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Considering the different moderators included in the three models, geographical location by country (3/3 models) and sample size (2/3) were the most statistically relevant predictors. The sample size may be a bias factor in small sample size studies, overestimating wildlife TB prevalence, as previously observed in the quantification of pooled TB prevalence in livestock (Ramos et al, 2020). The country variable proved to be an important moderator since specific wildlife hosts can be perceived as TB reservoirs in some countries (badgers in the UK, red deer and wild boar in the Iberian Peninsula and Central Europe), but spillover species in others.…”
Section: Overviewmentioning
confidence: 83%
“…Considering the different moderators included in the three models, geographical location by country (3/3 models) and sample size (2/3) were the most statistically relevant predictors. The sample size may be a bias factor in small sample size studies, overestimating wildlife TB prevalence, as previously observed in the quantification of pooled TB prevalence in livestock (Ramos et al, 2020). The country variable proved to be an important moderator since specific wildlife hosts can be perceived as TB reservoirs in some countries (badgers in the UK, red deer and wild boar in the Iberian Peninsula and Central Europe), but spillover species in others.…”
Section: Overviewmentioning
confidence: 83%
“…These studies were performed both by serology ( Table 7 ) and by isolation or direct identification of mycobacteria in organs and tissues ( Table 8 ). The prevalence of MTC varies between countries and between regions/counties inside each nation (e.g., Spain), but also due to the investigated matrix and the diagnostic methods adopted [ 94 , 98 , 135 ]. In this context, some studies were performed to define the sensitivity of different diagnostic tools on sera and on organs and tissues [ 94 , 96 , 119 , 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…The animal TB burden is highly variable across countries and continents, with main variations according to predominant livestock systems. Although the available data may be biased due to different sampling strategies and diagnostic capacities, the highest animal prevalence is reported from the Americas and Europe ( Ramos et al, 2020 ).…”
Section: Animal Tb Burdenmentioning
confidence: 99%
“…However, zTB disease is largely underreported and, these wide ranges are indicative of major diagnostic challenges and poor public health surveillance and reporting structures in endemic countries. The highest numbers were reported from Africa (68,900) and South East Asia (43,400) ( Ramos et al, 2020 ) ( WHO, 2020a ). South-East Asia comprises almost 44% of the global TB burden ( WHO, 2020a ).…”
Section: Zoonotic Tb Burdenmentioning
confidence: 99%